Surfactant systems for nasal zidovudine delivery: structural, rheological and mucoadhesive properties - Carvalho, Flavia C. [UNESP]; Barbi, Mariana S. [UNESP]; Sarmento, Victor Hugo V.; Chiavacci, Leila Aparecida [UNESP]; Netto, Flavia M.; Gremião, Maria Palmira Daflon [UNESP] (Wiley-Blackwell, 2010)
Objectives Zidovudine is the antiretroviral drug most frequently used for the treatment of AIDS. Although its effectiveness is recognized, it undergoes extensive first-pass metabolism and exhibits poor oral bioavailability. The nasal route is an option for enhanced therapeutic efficacy and to reduce the extent of the first-pass effect. There are some mechanisms that limit intranasal absorption, such as mucociliary clearance, which rapidly removes the formulation from the nasal cavity. To improve the nasal residence time of zidovudine on the nasal mucosa, we aimed to develop a mucoadhesive surfactant system for zidovudine nasal administration.Methods Systems composed of PPG-5-CETETH-20 as surfactant, oleic acid and water were characterized by polarized light microscopy, small-angle X-ray scattering and rheological measurements. Mucoadhesion was investigated by phase behaviour studies, rheological synergism and mucoadhesive strength determination.Key findings Results indicate that the original formulations were microemulsions that displayed phase transition to a lamellar phase when brought into contact with aqueous nasal simulated mucus. The phase transition was accompanied by an increase in system elasticity and, irrespective of phase behaviour, all the systems showed a good mucoadhesive force. Thus, a viscous and mucoadhesive liquid crystalline matrix could be formed when the formulations were in contact with simulated mucus, which may prolong the residence time of zidovudine in the nasal cavity.Conclusions These findings indicate a potentially useful system for nasal administration of zidovudine.
Keywords: liquid crystal; microemulsion; mucoadhesion; oscillatory rheology; phase behaviour